2021
DOI: 10.1016/j.wroa.2020.100079
|View full text |Cite
|
Sign up to set email alerts
|

Keeping water from kiosks clean: Strategies for reducing recontamination during transport and storage in Eastern Uganda

Abstract: Drinking water is frequently recontaminated during transport and storage when water is poured into jerrycans. To address this issue, three strategies aiming at reducing these recontamination risks were implemented at water kiosks in Eastern Uganda. In all three strategies, water at the kiosks was chlorinated to a free residual chlorine (FRC) concentration of 2 mg/L at the tap of the kiosk. In addition, water was collected in different containers for drinking water transport: a) uncleaned jerrycans, b) cleaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…coli was detected in 35% of these large reusable water containers. In other studies, containers with larger openings have been shown to be easier to clean, yielding lower microbial contamination levels . In this study, households who reported cleaning these containers with soap or hot water had lower levels of E.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…coli was detected in 35% of these large reusable water containers. In other studies, containers with larger openings have been shown to be easier to clean, yielding lower microbial contamination levels . In this study, households who reported cleaning these containers with soap or hot water had lower levels of E.…”
Section: Discussionmentioning
confidence: 53%
“…In other studies, containers with larger openings have been shown to be easier to clean, yielding lower microbial contamination levels. 65 In this study, households who reported cleaning these containers with soap or hot water had lower levels of E. coli in their drinking water than those who rinsed their containers with only water (data not shown). However, this should be interpreted with caution as the reporting of cleaning containers with soap and hot water could be inflated due to social desirability bias, which has been a traditional challenge in hygiene-related and environmental psychology research.…”
Section: Acs Esandt Watermentioning
confidence: 63%
“…Previous studies have indicated that the cleanliness of the container used for the transport and storage of drinking water is important for reducing the risk of contaminating water that is put in the containers ( Gärtner et al, 2021 ; Meierhofer et al, 2019 ; Wright et al, 2004 ). Our study contributes to the very limited evidence available on the association between safe storage and health.…”
Section: Discussionmentioning
confidence: 99%
“…If the chlorine demand of the water is high (> 1.3 mg/Lover 24 h), it may be difficult to find a chlorinator that consistently (:e: 90 per cent) guarantees :e: 0.2 mg/L PRC after 24 h of storage and at the same time does not interfere with taste acceptability (~2 mg/L). In this case, measures to reduce the chlorine demand are recommended; for example, safe storage containers (Roberts et al, 2001;Reed et al, 2011;Mellor et al, 2013;Gartner et al, 2020) or periodically cleaning and disinfecting the containers (Steele et al, 2008;Meierhofer et al, 2019;Gartner et al, 2020). 2.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%